Clinical effect of limited posterior decompression and 13-mm titanium mesh implantation on severe thoracolumbar burst fractures: A case series - Jingcheng, Liu; Lei, Lu (Frontiers in Surgery, 2023)
Background: Posterior incision with 270° spinal canal decompression and reconstruction surgery is a treatment option for thoracolumbar burst fractures (TLBF), but the large diameter titanium mesh placement is difficult. This study evaluated the characteristics and clinical effects of limited posterior decompression and 13-mm titanium mesh implantation to treat TLBF. Hypothesis: 13-mm titanium meshes could be used to fix thoracolumbar burst fractures. Patients and Methods: This case series included patients who underwent limited posterior decompression and 13-mm titanium mesh implantation at China Medical University Shaoxing Hospital (01/2015-12/2019). The Cobb angle, injury vertebral anterior edge height loss percentage, and spinal canal occupancy rate were analyzed. The degree of spinal cord injury was evaluated according to the ASIA grade. Results: Fifteen patients were included (eight males and seven females). The patients were 32.2±4.6 years of age. The American Association of Spinal Injury improved after surgery (A/B/C/D/E: from 2/6/5/2/0 to 0/0/2/8/5, P<0.001). The Cobb angle decreased after surgery (from 20.1±4.8° to 7.1±1.4°, P<0.001) but increased to 8.2±0.9° at 1 year (P=0.003). The percentage of loss of the anterior edge height of the injured vertebrae decreased after surgery (from 40.9%±6.1% to 7.5%±1.8%, P<0.001) and decreased at 1 year (7.0%±1.5%, P=0.044). The spinal canal occupancy rate decreased after surgery (from 64.8%±7.8% to 20.1%±4.2%, P<0.001) but did not decrease further at 1 year (19.4%±3.4%, P=0.166). Discussion: Spinal canal limited posterior decompression, and 13-mm titanium mesh implantation in the treatment of TLBF can achieve one-stage spinal canal decompression and three-column reconstruction. The curative effect was satisfying.